2014
DOI: 10.3389/fnhum.2014.00058
|View full text |Cite
|
Sign up to set email alerts
|

Insight into others’ minds: spatio-temporal representations by intrinsic frame of reference

Abstract: Recent research has seen a growing interest in connections between domains of spatial and social cognition. Much evidence indicates that processes of representing space in distinct frames of reference (FOR) contribute to basic spatial abilities as well as sophisticated social abilities such as tracking other’s intention and belief. Argument remains, however, that belief reasoning in social domain requires an innately dedicated system and cannot be reduced to low-level encoding of spatial relationships. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…Individuals adopt multiple frames of reference (FORs) to represent spatial relationships of objects in complex environments (Levinson, ). Although many approaches are available to classify FORs (Levinson, ), in this study, we adopted a classification system based on psycholinguistic research (Sun & Wang, ) that involves an egocentric FOR (EFOR), intrinsic FOR (IFOR), and allocentric FOR (AFOR). EFOR‐based representations are anchored to the observer and must be updated following the movement of the observer's eye, head, and body coordinates (H. Wang, Johnson, & Zhang, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Individuals adopt multiple frames of reference (FORs) to represent spatial relationships of objects in complex environments (Levinson, ). Although many approaches are available to classify FORs (Levinson, ), in this study, we adopted a classification system based on psycholinguistic research (Sun & Wang, ) that involves an egocentric FOR (EFOR), intrinsic FOR (IFOR), and allocentric FOR (AFOR). EFOR‐based representations are anchored to the observer and must be updated following the movement of the observer's eye, head, and body coordinates (H. Wang, Johnson, & Zhang, ).…”
Section: Introductionmentioning
confidence: 99%
“…In AFOR‐based representations, the entire environment, such as a room or city, is considered the reference point. This categorical system may reduce ambiguity in spatial descriptions of the world and promote the understanding of human spatial cognition (Majid, Bowerman, Kita, Haun, & Levinson, ; Mou & McNamara, ; Sun & Wang, ; Tamborello, Sun, & Wang, ). Notably, different people may use different FORs to describe the same spatial situation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The statistical analyses reported in the correspondence article are in the same line by examining nonstationarity in the players' performance based on local "racks." It has been suggested that temporal instability in the task environment is the driving force for predictive learning, which eventually leads to complex achievements such as thought, language, and intelligence (Hawkins & Blakeslee, 2004;O'Reilly, Munakata, Frank, Hazy, & Contributors, 2012;Sun & Wang, 2013b). In this regard, we argue that computational models of human probabilistic reasoning, such as the hot hand belief, have the potential to capture the properties of human cognition in accordance with the statistical structures in the task environment.…”
mentioning
confidence: 99%